Building a More Resilient Nepal-The Utilisation of the Resilience Scorecard for Kathmandu, Nepal following the Gorkha Earthquake of 2015 - M.R.Z. Whitworth; A. Moore; M. Francis; S. Hubbard; S. Manandhar (International Association of Lowland Technology, 2020)
Following the Gorkha earthquake of 2015, the opportunity exists to utilise the Resilience Scorecard to assess the current level of preparedness of Kathmandu. This article will discuss the application of the UN Resilience Scorecard, with the assessment undertaken forming a baseline assessment addressing core infrastructure issues from the earthquake and evaluating core community functions. The assessment looks at initially 3 pillars of the Resilience Scorecard through 3 core components: 1. The disaster cycle: From preparedness through response recovery to developing risk scenarios. 2. The operational capacity of the financial, governmental and societal institutions. 3. The resilience of the society from urban to rural including infrastructure and natural buffers. This paper highlights the key findings of the assessment undertaken during field visits to Kathmandu Valley following the April 2015 earthquake. The research study has found that Kathmandu has a low disaster resilience score with preliminary findings highlighting the susceptibility of critical infrastructure (i.e. roads, schools, hospitals, power, water supply) to natural hazards.